Same kind of different as me - Hall, Ron, 1945- (Thomas Nelson, 2006)
The co-author relates how he was held under plantation-style slavery until he fled in the 1960s and suffered homelessness for an additional eighteen years before the wife of the other co-author, an art dealer accustomed to privilege, intervened.